TRIG on TRACK: educating pathology residents in genomic medicine. (May 2012) - Haspel, Richard L; Atkinson, James B; Barr, Frederic G; Kaul, Karen L; Leonard, Debra GB; O'Daniel, Julianne; Rinder, Henry M; Scott, Joan; Sobel, Mark E; Speights, VO
Genomic technologies are dramatically changing the practice of medicine. Next-generation sequencing has allowed prognostic stratification of cancer patients, personalized drug therapy and the identification of genetic risk factors for a multitude of diseases. As the physicians who oversee tissue- and laboratory-based diagnostic testing, pathologists must understand and utilize this new technology for the benefit of patients; however, only a minority of pathology residency programs currently provide training in genomics. In response to this urgent need, the Training Residents in Genomics (TRIG) Working Group has made significant progress towards creating, implementing, evaluating and disseminating a national curriculum in genomic pathology. Although presented in the context of pathology training, the approach described in this review can serve as model for education in genomic medicine of students, trainees or professionals in other areas of healthcare.